"Walking with Only Non-Invasive Ventilation in Stable Hypercapnic COPD Patients: Sufficient or Not?". (3rd July 2016) - Walker, David J.; Windisch, Wolfram; Dreher, Michael
ABSTRACT: We are grateful to Ulasli and Esquinas for their comments to our paper.. They argued that arterial blood gas analyses were not performed without oxygen prior to the 6-minute walk test with noninvasive ventilation (6MWT-NPPV). This point has already been discussed in our original work by indicating the limitations of our study. The reason for using oxygen prior to exercise testing was to guarantee comparable starting conditions.